Tolerability of FODMAP – reduced diet in irritable bowel syndrome – efficacy, adherence, and body weight course - Frieling, Thomas; Heise, Jürgen; Krummen, Britta; Hundorf, Corinna; Kalde, Sigrid (Zeitschrift für Gastroenterologie, 2019)
Background FODMAP reduced diet (fermentable oligo-, di-, monosaccharide, and polyols) belongs to the established therapy strategies in irritable bowel syndrome (IBS). However, disadvantages of this diet are significant and may lead to weight loss and insufficient patient adherence. Reports from Germany are not available yet.Material and methods In a prospective study, 93 patients with IBS according to Rom III were investigated. Sixty-three patients were recruited for the study and received standardized investigation, informed consent, and structured dietary instructions about the FODMAP reduced diet. Patients complaints were documented by a validated questionnaire and a standardized Lickert scale before and 8 weeks after the start of the diet. Stool characteristics were documented by the Bristol stool form scale.Results Patients adherence was low because 30 patients (47 %) stopped the diet. Of the remaining 33 patients, 36 % (n = 12) developed significant weight loss during the FODMAP therapy. Patients completing the study reported significant global improvement of symptoms in 79 % of cases (abdominal pain 85 %, meteorism 79 %, flatulence 69 %, borbogymi 69 %, nausea 46 %, fatigue 69 %). In addition, the severity of symptoms was significantly reduced. Fourteen patients developed changes of their stool characteristics according to the Bristol stool form scale, 11 of whom improved diarrhea and 3 improved constipation.Conclusion FODMAP reduced diet is an efficient therapy in IBS. However, adherence of the patients is poor and the therapy bears the risk of significant weight loss.
Keywords: FODMAP; irritable bowel syndrome; IBS